ETNOZOOLOGI MASYARAKAT DAYAK JELAI HULU EMBULU LIMA DI DESA MEKAR UTAMA KECAMATAN KENDAWANGAN KABUPATEN KETAPANG - Sunaryo, Eko; Anwari, M Sofwan; Yani, Ahmad (JURNAL HUTAN LESTARI, 2019)
The use of fauna has been carried out by various ethnic groups in Kalimantan for a long time to fulfill their daily needs, one of which is as a source of food, medicine, ritual facilities, mysticism and art. The Dayak Jelai Hulu Embulu Lima tribe located in Mekar Utama Village, Kendawangan District are one of the original ethnic groups of West Kalimantan, also have diversity in the use of fauna both for food, medicine, traditional and supernatural ceremonies. The purpose of this study is to list the types of animals that are used and examine the use of animals. Data collection techniques are done by in-depth interviews with selected respondents using survey methods. The selection of respondents was carried out using snowball sampling techniques. Respondents in this study were 9 people. The interview results obtained as many as 48 types of data used in the village. Utilization varies starting from the utilization of consumption of as many as 35 animals, which has 9 artistic values, for the treatment of 12 animals, as much as 4 mystical animals, and for rituals as many as 3 animals. Based on the high percentage of species of animals utilized by the Embulu Lima Upper Barley community, namely consumption. The high percentage of consumption utilization is 58%, the part that is used is meat and the way it is processed is more cooked and fried. Meeting the needs of the most protein is from game animals. Utilization of animals for the treatment of ways such as, among others, drunk, smeared, and eaten. Processing methods include drying, scraping, diluting and cooking.Keywords: Dayak Jelai Hulu Embulu Lima, Ethnozoolgy, Utilization.